2005
DOI: 10.1258/095646205774357299
|View full text |Cite
|
Sign up to set email alerts
|

A review of controlled trials in the pharmacological treatment of premature ejaculation

Abstract: Premature ejaculation is a common sexual problem which presents to genitourinary (GU) medicine services. Five main treatment approaches have been used in clinical trials: behavioural therapy, antidepressants, phosphodiesterase-5 (PDE5) inhibitors, topical anaesthetic agents and alpha-blockers. We have carried out a systematic review of published pharmacological trials. All antidepressants appeared to delay ejaculation to some extent at all doses. Anaesthetic creams appeared to be as successful in slowing ejacu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 0 publications
0
10
0
1
Order By: Relevance
“…64,65,67 One review was conducted in Australia, 68 one in the Netherlands, 52 one in the USA 66 and one in the UK. 69 The overall AMSTAR quality score was 1 out of 11 in three of the reviews, 52,65,69 2 out of 11 in one review 68 and 3 out of 11 in one review. 64 Two reviews scored 0 out of 11.…”
Section: Assessment Of Clinical Effectivenessmentioning
confidence: 89%
See 3 more Smart Citations
“…64,65,67 One review was conducted in Australia, 68 one in the Netherlands, 52 one in the USA 66 and one in the UK. 69 The overall AMSTAR quality score was 1 out of 11 in three of the reviews, 52,65,69 2 out of 11 in one review 68 and 3 out of 11 in one review. 64 Two reviews scored 0 out of 11.…”
Section: Assessment Of Clinical Effectivenessmentioning
confidence: 89%
“…Eight further RCTs [124][125][126][127][128][129][130][131] that also evaluated oral clomipramine were identified from three reviews of low methodological quality. 52,68,69 Full details of the AMSTAR assessment for these and all other included reviews are presented in Appendix 4. A further three RCTs were identified from the literature search, 107,132,133 and the RCT by Tuncel et al 107 evaluated clomipramine, sertraline, terazosin and placebo.…”
Section: Characteristics Of Included Studies: Tricyclic Antidepressantsmentioning
confidence: 99%
See 2 more Smart Citations
“…For SSRIs, eleven existing reviews were identified and it was possible to check the data across these reviews for concordance (Cong et al 2012;Huang et al 2009;Luo et al 2012;McCarty and Dinsmore 2012;McMahon 2012;McMahon and Porst 2011;Moreland and Makela 2005;Richardson et al 2005;Waldinger et al 2004a;Wang et al 2007;Wang et al 2010). Outcome data from RCTs not reported in reviews was extracted from the RCT publication.…”
Section: Data Extraction For Rapid Reviewmentioning
confidence: 99%